MUSEUM TOSAN AJI DI PURWOREJO - Astri Prihastuti; Muhammad Muqoffa; Tri Yuni Iswati (Universitas Sebelas Maret Surakarta, 2017)
Tosan Aji Museum in Purworejo is a built space in Purworejo Regency. It serves the purpose of keeping, preserving, and displaying the tosan aji, an umbrella term referrring to any esteemed metal works which comprises of keris (the most renowned metal work), spear, sword, kudi, and menur for education and recreation purposes. The problem to be tackled during the design process is to accomplish the intents of exhibiting the tosan aji to the general public. The expressive designs focuses on the building's physical aspects ( room, form and massing, facade, and interior) to show an intention or aim – presents on the visual level – in achieving the purposes of Tosan Aji Museum ini Purworejo.